TRANSFORMATION SEMIGROUPS AND TRANSFORMED DIMENSIONS (Journal of Sciences, Islamic Republic of Iran)
In the transformation semigroup (X, S) we introduce the height of a closed nonempty invariant subset of X, define the transformed dimension of nonempty subset S of X and obtain some results and relations.